Size-Dependent Hydrogen Oxidation and Evolution Activities on Supported Palladium Nanoparticles in Acid and Base. Issue 6 (1st January 2016) - Zheng, Jie; Zhou, Shuyuan; Gu, Shuang; Xu, Bingjun; Yan, Yushan
Abstract : The study of particle size effect provides the fundamental understanding of the active sites that is necessary for guiding the design and development of better catalysts. Here we report a systematic investigation of particle size effect of hydrogen oxidation and evolution reaction (HOR/HER) on carbon supported Pd nanoparticles with sizes ranging from 3 to 42 nm in both acidic and alkaline electrolytes using rotating disk electrode (RDE) method. Similar particle size effect was obtained in both acid and base: the HOR/HER activity in terms of specific exchange current density increases as Pd particle size increases from 3 to 19 nm, and then reaches a plateau with activity similar to that of bulk Pd. The enhanced activity with rising particle size could be attributed to the increased ratio of the sites with weaker hydrogen binding energy revealed in cyclic voltammograms (CVs). Pd catalysts with different Pd particle sizes all showed much higher HOR/HER activity in acid than in base, which is largely attributed to their smaller hydrogen binding energy in acid evidenced by the lower potential of the underpotential deposited hydrogen (Hupd ) peak in CVs as well as the smaller activation energy in acid.